(untitled) (Economic Journal of Nepal, 2024)
This paper assesses the monetary policy responses to the stock market performance of Nepal. This study employs the augmented Taylor rule using the quarterly time series data for the period 2004-2022 to estimate the monetary policy response for the stock market performance where the interest variables are the NEPSE index and the short-term interest rate while the output gap and inflation are the control variables. The output gap has been estimated using Hodric-Perscott filter. The consumer price index has been used as a measure of inflation and the 91-day T-bill rate and interbank rate are taken as the proxy for the short-term interest rate set by the Central Bank of Nepal. The ARDL Bounds Test results show that the computed F-statistics for T-bill rate (2.410678) and interbank rate (2.605799), with logNEPSE as the explanatory variable, fall below the lower bound critical value I(0) at both 1% and 5% significance levels. This fails to reject the null hypothesis, indicating no cointegration and suggesting no long-run relationship between the variables. Consequently, a VAR model was employed to explore the short-run dynamics. The Block Exogeneity Wald test was conducted to assess Granger causality between monetary policy instruments (interbank rate and 90-day T-bill rate) and stock prices (NEPSE index). The results indicate that logNEPSE does not Granger cause either the T-bill rate or the interbank rate. However, both interest rates are found to Granger cause NEPSE, demonstrating a unidirectional causal relationship from monetary policy instruments to stock prices. This indicates that the central bank of Nepal does not respond to NEPSE. However, NEPSE reacts to the changes in the monetary policy of the Central Bank.